2018
DOI: 10.1159/000492541
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Increases the Sensitivity of Photodynamic Therapy Via NF-κB/HIF-1α/VEGF Pathway in Esophageal Cancer Cell in vitro and in vivo

Abstract: Background/Aims: Although photodynamic therapy (PDT) can relieve esophageal obstruction and prolong survival time of patients with esophageal cancer, it can induce nuclear factor-kappa B (NF-κB) activation in many cancers, which plays a negative role in PDT. Dihydroartemisinin (DHA), the most potent artemisinin derivative, can enhance the effect of PDT on esophageal cancer cells. However, the mechanism is still unclear. Methods: We generated stable cell lines expressing the super-repressor form of the NF-κB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…DHA also reinforces the anti-cancer activity of chemotherapeutic agent, cisplatin, in cisplatin-resistant ovarian cancer cells [215]. Studies also demonstrate the enhancement of sensitivity by DHA in photodynamic therapy in esophageal cancer [182,216]. Therefore, this suggests that ARTs could be potential anti-cancer agents.…”
Section: Artemisininsmentioning
confidence: 77%
See 1 more Smart Citation
“…DHA also reinforces the anti-cancer activity of chemotherapeutic agent, cisplatin, in cisplatin-resistant ovarian cancer cells [215]. Studies also demonstrate the enhancement of sensitivity by DHA in photodynamic therapy in esophageal cancer [182,216]. Therefore, this suggests that ARTs could be potential anti-cancer agents.…”
Section: Artemisininsmentioning
confidence: 77%
“…Since the 2015 Nobel Prize in Physiology or Medicine conferred to Chinese scientist, Youyou Tu, artemisinin drew attention to worldwide [176]. Beside from their well-established anti-malarial effects, artemisinin and its derivatives (ARTs), including dihydroartemisinin (DHA), artesunate, artemether and arteether, are also found to exhibit potent anti-cancer activities in many studies [177][178][179][180][181][182]. DHA and artesunate are the most studied ART derivatives for cancer treatment, and artesunate will be discussed in a separate section.…”
Section: Artemisininsmentioning
confidence: 99%
“…In this study, we assume VEGF was regulated in two ways. It has been reported that NFκB signaling induces angiogenesis by increasing the production of VEGF [44][45][46], angiogenesis induced by MUC3A is also mediated by NFκB activation in NSCLC. Radiation-mediate hypoxia triggers HIF-1α transcription and up-regulates VEGF expression [46,47], MUC3A knockdown may enhance radiosensitivity by promoting oxygen stress and impair HIF-1α and VEGF expression level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NFκB signaling induces angiogenesis by increasing the production of VEGF [44][45][46], angiogenesis induced by MUC3A is also mediated by NFκB activation in NSCLC. Radiation-mediate hypoxia triggers HIF-1α transcription and up-regulates VEGF expression [46,47], MUC3A knockdown may enhance radiosensitivity by promoting oxygen stress and impair HIF-1α and VEGF expression level. Furthermore, MMP-2 and MMP-9 are also known to stimulate tumor angiogenesis and the epithelial-to-mesenchymal transition (EMT) through partial proteolysis of the ECM [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, DHA induces apoptosis in human HCC cells harboring p53-null, wild-type (WT) p53, and mutant p53, respectively [23]. Furthermore, the combination of DHA and other chemotherapeutic agents plays a synergistic role in the treatment of many kinds of cancers [24,25]. However, whether DHA could enhance the sensitivity of p53 (R248Q)-expressing HCC cells to ADM and the underlying mechanism remains unknown.…”
Section: Introductionmentioning
confidence: 99%